2019
DOI: 10.3892/etm.2019.8141
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effect of the interaction of fluoxetine with granisetron

Abstract: Selective serotonin reuptake inhibitors (SSRIs) may produce digestive side effects such as nausea and vomiting, diarrhoea and decreased appetite. These side effects are determined by the increase in serotonin availability at 5-HT3 receptors. Granisetron, a serotonin 5-HT3 receptor antagonist, is expected to antagonize the digestive adverse effects of serotonin reuptake inhibitors, but the question is to what extent granisetron influences the antidepressant effect of these substances. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Fluoxetine however, decreased the immobility time, which supports previous studies (Abdel-Salam et al 2013). Furthermore, fluoxetine increased mobility time in the FST (Costescu et al 2019), which the present study aligns. The potency of fluoxetine in the FST is based on its ability as a selective serotonin reuptake inhibi- tor, demonstrated in alleviating behavioural depression, and possibly due to its ability to suppress cholinergic activities in the nucleus accumbens, or by inhibition of noradrenaline and dopamine reuptake.…”
Section: Discussionsupporting
confidence: 89%
“…Fluoxetine however, decreased the immobility time, which supports previous studies (Abdel-Salam et al 2013). Furthermore, fluoxetine increased mobility time in the FST (Costescu et al 2019), which the present study aligns. The potency of fluoxetine in the FST is based on its ability as a selective serotonin reuptake inhibi- tor, demonstrated in alleviating behavioural depression, and possibly due to its ability to suppress cholinergic activities in the nucleus accumbens, or by inhibition of noradrenaline and dopamine reuptake.…”
Section: Discussionsupporting
confidence: 89%
“…Considering that the first onset of action of antidepressants is between 2 and 4°weeks ( 46 ), We, therefore, chose to collect the subjects’ depression scores at three-time points: baseline, week 3 of the intervention and week 6 of the intervention. The scales were selected based on clinical applicability and reliability to dynamically assess the efficacy of the localized PEERS training.…”
Section: Materials and Methods And Analysismentioning
confidence: 99%
“…Granisetron is an antagonist of this receptor and its activity can alleviate gastrointestinal disorders associated with the use of SSRIs. At low doses, an increase in the antidepressant action of fluoxetine is also observed when administered in conjunction with granisetron [ 114 ]. A previous study has shown that other antidepressants such as imipramine, phenelzine, and iproniazid are able to inhibit the serotonergic current mediated by the 5-HT 3 receptor, blocking its action.…”
Section: 5-ht 3 Receptorsmentioning
confidence: 99%